2013
DOI: 10.3390/en6126225
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Dissociation of Methane Hydrates from Seawater in Consolidated Sand: Mimicking Methane Hydrate Dynamics beneath the Seafloor

Abstract: Methane hydrate formation and dissociation kinetics were investigated in seawater-saturated consolidated Ottawa sand-pack under sub-seafloor conditions to study the influence of effective pressure on formation and dissociation kinetics. To simulate a sub-seafloor environment, the pore-pressure was varied relative to confining pressure in successive experiments. Hydrate formation was achieved by methane charging followed by sediment cooling. The formation of hydrates was delayed with increasing degree of consol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…This method is the easier and simpler method to estimate the enthalpy of dissociation. Using the Clausius-Clapeyron equation which is stated below [14]:…”
Section: Measurement Methods Of Clathrate Hydrate Dissociation Enthalmentioning
confidence: 99%
“…This method is the easier and simpler method to estimate the enthalpy of dissociation. Using the Clausius-Clapeyron equation which is stated below [14]:…”
Section: Measurement Methods Of Clathrate Hydrate Dissociation Enthalmentioning
confidence: 99%
“…1, 2019 transfer for the formation of hydrate and dissociation [4]. The more commonly studies of hydrates guest molecules are for the light hydrocarbons like propane and isobutene and most low molecular weight gases, including hydrogen, CO2, hydrogen sulfide and nitrogen [5]. Refrigerant hydrates can be formed at lower temperature and under low pressures and can be considered in the desalination process, also favorable materials for energy storage, and that considered favorable in air conditioning systems.…”
Section: Engineering and Technology Journalmentioning
confidence: 99%
“…Prasad et al studied the kinetics of dissociation of methane hydrates by stepwise depressurization at a set bath temperature. 23 Researching methane hydrate dissociated under backpressures that were varied from 2.8 to 2.2 MPa, Wang et al 24 found that the dissociation rate of a hydrate that was dissociated by a continuous depressurization was higher than that dissociated by a constant backpressure, and the impact of the initial backpressure difference on the hydrate dissociation rate was almost negligible for continuous backpressure. However, during the decomposition of hydrate, the rate of gas hydrate is slower and slower as time progresses, which is not cost saving.…”
Section: Introductionmentioning
confidence: 99%